PENGARUH MODEL PBL TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA KELAS V SEKOLAH DASAR - Yuliana, Yuliana; Kresnadi, Hery; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the effect of the use of problem based learning models on the learning outcomes of Natural Sciences class V Pontianak Elementary School 05 City. The method used is the experimental method, while the form of the study used experimental design with nonequivalent control group design. The population and sample in this study were all fifth grade students of Elementary School 05 City of Pontianak. The data tool used is a multiple choice test with 45 questions. Based on data analysis, the average post-test results of the experimental class were 75.45 while the post-test average of the control class was 63.90. The results of the t test are obtained tcount 4,284 and t table Î± = 5% (with dk = 21 + 20 - 2 = 39) of 2,023, which means tcount (4,284)> t table (2,023), then the alternative hypothesis (Ha) can be accepted. It can be concluded that there is the influence of the use of problem based learning models on learning outcomes in learning Natural Sciences class V public elementary school Pontianak 05 City. From the calculation of effect size (ES) ES obtained is 0.97 (high criteria). It can be concluded that learning outcomes by applying a problem based learning model in class V of Pontianak City primary school 05 have a high influence.Â Keywords: Problem Based Learning, Learning Outcomes, Natural Sciences.Â